Hypoxemia Event and Related Factor on Diagnostic Bronchoscopy for Lung Tumor Case - Andre Prawira Putra; Menaldi Rasmin; Wahju Aniwidyaningsih (Jurnal Respirologi Indonesia, 2020)
Background: Bronchoscopy is a commonly medical procedure perfomed for diagnose lung tumor cases. Hypoxemia often appear as complication related diagnostic bronchoscopy. Therefore, there is a need of research data to knowing related factors and clinical consequences may occur ahead. Methods: Design of this study is cross sectional with suspicion lung malignancy population who undergoing diagnostic bronchoscopy from January until april 2019 at National Respiratory Center Persahabatan General Hospital Jakarta. Total 195 consecutive patients participated dan observed for oxygen saturation in premedication, during and post-bronchoscopy. Hypoxemia was defined as a desaturation